STRATEGI GURU DALAM MENINGKATKAN FOKUS BELAJAR ANAK TUNA GRAHITA DI SLB SAMUDERA LAVENDER - Shinta Nuriah; ST. Shafiyatul Hasanah; Fara Medinna Oktavia; Vero Stantika; Nova Estu Harsiwi (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT Special education for students with intellectual disabilities requires adaptive learning strategies, as these students experience limitations in intellectual functioning, communication, and emotional regulation that may affect the learning process. Therefore, teachers need to implement instructional strategies that are tailored to the individual needs and abilities of each student. This study aims to describe the learning strategies employed by teachers in assisting students with intellectual disabilities at Samudra Lavender Special School. This study employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. The findings revealed that teachers applied direct instruction, habituation, learning through play, and the use of engaging learning media to help students understand the learning materials. In addition, teachers modified the curriculum and implemented Individualized Education Programs (IEPs) according to students' abilities. Learning evaluation was conducted by observing students' behavioral development, communication skills, motor skills, and independence. The obstacles encountered included limited school facilities and students' unstable emotional conditions. To overcome these challenges, teachers provided gradual assistance and collaborated with parents and therapists. The study concludes that adaptive learning strategies, effective communication, and positive environmental support play an important role in improving the abilities and independence of students with intellectual disabilities. ABSTRAK Pendidikan khusus bagi siswa tunagrahita memerlukan strategi pembelajaran yang adaptif karena siswa memiliki hambatan intelektual, komunikasi, dan pengendalian emosi yang dapat memengaruhi proses belajar. Oleh karena itu, guru perlu menerapkan strategi yang sesuai dengan kebutuhan dan kemampuan masing-masing siswa. Penelitian ini bertujuan untuk mendeskripsikan strategi pembelajaran guru dalam mendampingi siswa tunagrahita di SLB Samudra Lavender. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa guru menerapkan strategi pembelajaran langsung, pembiasaan, bermain sambil belajar, serta penggunaan media pembelajaran yang menarik untuk membantu siswa memahami materi. Selain itu, guru melakukan modifikasi kurikulum dan menerapkan Program Pembelajaran Individual (PPI) sesuai dengan kemampuan siswa. Evaluasi pembelajaran dilakukan melalui pengamatan terhadap perkembangan perilaku, kemampuan komunikasi, motorik, dan kemandirian siswa. Hambatan yang ditemukan meliputi keterbatasan fasilitas sekolah dan kondisi emosi siswa yang kurang stabil. Untuk mengatasi hambatan tersebut, guru memberikan pendampingan secara bertahap serta menjalin kerja sama dengan orang tua dan terapis. Penelitian ini menyimpulkan bahwa strategi pembelajaran yang adaptif, komunikasi yang efektif, dan dukungan lingkungan yang positif berperan penting dalam meningkatkan kemampuan dan kemandirian siswa tunagrahita.